Operasi Lancar, Hati Bugar: Rahasia Sukses Persiapan Operasi Melalui Edukasi Tepat Guna - Rahayu Setyaningsih; Aprilia Nuryanti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Abstract Introduction: Pre-operative anxiety and patients' lack of knowledge regarding surgical preparation procedures often hinder the smoothness of anesthesia administration and post-operative recovery. Appropriate health education is necessary to improve patient compliance with pre-surgical protocols, such as fasting and personal hygiene, thereby minimizing the risk of intraoperative complications. Methods: This community service activity took the form of health counseling and the distribution of educational media in the form of a "Ready for Surgery" booklet to 50 patients scheduled for elective surgery at RSUD X. The methods used included interactive lectures, demonstrations of deep breathing relaxation techniques, and evaluation of understanding through pre-test and post-test questionnaires. Results: There was a significant increase in participants' knowledge scores regarding pre-operative preparation, from an average of 45% (pre-test) to 85% (post-test). As many as 90% of participants stated they felt calmer and more confident facing the surgical procedure after receiving the education. Compliance with fasting instructions and personal hygiene also increased drastically compared to historical data prior to the intervention. Discussion: Providing clear, simple, and visual information helps reduce anxiety and improves patients' understanding of the importance of physical preparation. Two-way interaction during the counseling allowed for the clarification of myths circulating in the community regarding surgical preparation. Conclusion: Precise education through a multimedia approach and therapeutic communication effectively increases patients' mental and physical readiness, thereby supporting the smoothness of the surgical process and accelerating the recovery period.. Keywords : Pre-operative Education, Surgical Preparation, Patient Anxiety, Compliance, Community Service Abstrak Pendahuluan: Kecemasan pra-operasi dan ketidaktahuan pasien mengenai prosedur persiapan bedah sering kali menghambat kelancaran tindakan anestesi dan pemulihan pasca-operasi. Edukasi kesehatan yang tepat guna diperlukan untuk meningkatkan kepatuhan pasien terhadap protokol pra-bedah, seperti puasa dan higiene diri, sehingga dapat meminimalkan risiko komplikasi intraoperatif. Metode: Kegiatan pengabdian masyarakat ini berbentuk penyuluhan kesehatan dan distribusi media edukasi berupa booklet "Siap Operasi" kepada 50 pasien yang dijadwalkan menjalani operasi elektif di RSUD X. Metode yang digunakan meliputi ceramah interaktif, demonstrasi teknik relaksasi napas dalam, dan evaluasi pemahaman melalui kuesioner pre-test dan post-test. Hasil: Terjadi peningkatan signifikan pada skor pengetahuan peserta mengenai persiapan pra-operasi dari rata-rata 45% (pre-test) menjadi 85% (post-test). Sebanyak 90% peserta menyatakan merasa lebih tenang dan percaya diri menghadapi tindakan bedah setelah menerima edukasi. Kepatuhan terhadap instruksi puasa dan kebersihan diri juga meningkat drastis dibandingkan data historis sebelum intervensi. Pembahasan: Pemberian informasi yang jelas, sederhana, dan visual membantu mengurangi kecemasan serta memperbaiki pemahaman pasien tentang pentingnya persiapan fisik. Interaksi dua arah selama penyuluhan memungkinkan klarifikasi mitos yang beredar di masyarakat mengenai persiapan operasi. Kesimpulan: Edukasi tepat guna melalui pendekatan multimedia dan komunikasi terapeutik efektif meningkatkan kesiapan mental dan fisik pasien, sehingga mendukung kelancaran proses pembedahan dan mempercepat masa pemulihan. Kata Kunci: Edukasi Pra-Operasi, Persiapan Bedah, Kecemasan Pasien, Kepatuhan, Pengabdian Masyarakat *Penulis Korespondensi : Rahayu Setyaningsih *Email : rahayusetyaningsih@uhb.ac.id